Birth controls (contraceptive) methods and human immunodeficiency virus/sexually transmitted infections risk perception among Namibian university students - Jenyo, Toyin O.; Ojiezeh, Tony I. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The question of why are so many of these young girls getting pregnant, is routinely asked, and sometimes contemptuously answered. Accurate information on effectiveness, failures and side effects of different methods of contraception use, have direct relation with the level of their usage among teaming youths. Methods: Data was collected using self-completed questionnaires for quantitative cross-sectional survey among students in classes selected through simple random sampling in each stratum (University Campus). Relationship between independent variables (method of contraception, misconceptions about the role of contraceptives in preventing HIV/STIs and Risk of infections) and dependent variable (multiple sexual partners) was measured using multivariate model of logistic regression analysis. Results: The most common contraceptive methods used by students or their partners were condom (71%), withdrawal (20.6%), and birth control pills (7.2%), only 2% used other methods as birth control method, in spite of that, 6.3% got pregnant or impregnated someone. There was a high incidence of multiple sexual partners among the respondents, only 23.3% of the respondents believed they were at risk of HIV/STIs infections, while 40.0% believed they were not at risk, 36.7% were not definite of their risk status and only 79.9% of the participants have tested for HIV infection to determine their status. Conclusions: The most important factor influencing the choice of contraceptive method among young people is its efficacy in prevention of pregnancy. Unprotected sex may not only lead to unplanned pregnancy but HIV/STIs infections and the risk of infection is increased with multiple sexual partners. Thus, the real need for early education on sex and sexuality and also suggest that Government at all level should step-up campaign on contraceptive use and associated risk of non-compliance.